Prognostic Role of Combined EGFR and Tumor-Infiltrating Lymphocytes in Oral Squamous Cell Carcinoma - Wongpattaraworakul, Wattawan; Gibson-Corley, Katherine N.; Choi, Allen; Buchakjian, Marisa R.; Lanzel, Emily A.; Rajan KD, Anand; Simons, Andrean L. (Frontiers in Oncology, 2022)
Background Epidermal growth factor receptor (EGFR) is well known as a general prognostic biomarker for head and neck tumors, however the specific prognostic value of EGFR in oral squamous cell carcinoma (OSCC) is controversial. Recently, the presence of tumor-infiltrating T cells has been associated with significant survival advantages in a variety of disease sites. The present study will determine if the inclusion of T cell specific markers (CD3, CD4 and CD8) would enhance the prognostic value of EGFR in OSCCs. Methods Tissue microarrays containing 146 OSCC cases were analyzed for EGFR, CD3, CD4 and CD8 expression using immunohistochemical staining. EGFR and T cell expression scores were correlated with clinicopathological parameters and survival outcomes. Results Results showed that EGFR expression had no impact on overall survival (OS), but EGFR-positive (EGFR+) OSCC patients demonstrated significantly worse progression free survival (PFS) compared to EGFR-negative (EGFR-) patients. Patients with CD3, CD4 and CD8-positive tumors had significantly better OS compared to CD3, CD4 and CD8-negative patients respectively, but no impact on PFS. Combined EGFR+/CD3+ expression was associated with cases with no nodal involvement and significantly more favorable OS compared to EGFR+/CD3- expression. CD3 expression had no impact on OS or PFS in EGFR- patients. Combinations of EGFR/CD8 and EGFR/CD4 expression showed no significant differences in OS or PFS among the expression groups. Conclusion Altogether these results suggest that the expression of CD3+ tumor-infiltrating T cells can enhance the prognostic value of EGFR expression and warrants further investigation as prognostic biomarkers for OSCC.